Optimizing Sunscreen Safety: The Impact of TiO2 Particle Size on Toxicity and Biocompatibility - Adriana S. Maddaleno; Clàudia Casellas; Elisabet Teixidó; Laia Guardia-Escote; Maria Pilar Vinardell; Montserrat Mitjans (Nanomaterials)
The use of UV filters is a well-established strategy for preventing skin cancer and photoaging. Among inorganic filters, titanium dioxide (TiO2) provides excellent protection against both UVA and UVB radiation. Moreover, the use of such inorganic filters at the nano-sized scale has increased their acceptability because it ensures the cosmetically desired transparency in sunscreens that consumers demand. However, concerns remain regarding the potential toxicity of TiO2 nanoparticles, and discussion about their use in pharmaceuticals and cosmetics is still in progress. Their increased (bio)reactivity compared to bulk materials may lead to DNA damage. Furthermore, their capacity to cross dermal, respiratory, and gastrointestinal membranes remains a subject of debate. This study is therefore designed to assess and contrast the toxicological characteristics of a pair of commercially available titanium (IV) oxide sunscreens differing in particle size—microscale versus nanoscale. First, the morphology and hydrodynamic diameter of the TiO2 nanoparticles were characterized. Then, potential interactions and/or interferences of these nanoparticles with the methods used to evaluate cytotoxic behavior were studied. Finally, the hemocompatibility, cytotoxicity, phototoxicity, and genotoxicity of both micro- and nano-sized TiO2 were evaluated using human keratinocytes.